THE IMPORTANCE OF PROPER NOUNS IN PHRASEOLOGY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Phraseology has come to occupy an ever more central role in linguistic studies. It has embraced numerous, often interacting, theoretical approaches and has generated practical applications in areas from language teaching to translation and the production of ever more accurate lexicographic tools. Among the currents of research that have arisen within phraseology, that of contrastive, or comparative, phraseology has seen intense development since the 1960s, although a historical-comparative tradition involving examination of the evolution and etymology of mainly proverbs and sayings, dates back to the end of the 19th century [2;219]. Fifty years on, comparative phraseology can rightly be considered one of the mainstays of phraseology, a rich source of inspiration for research that in turn opens new perspectives for further investigation [3;191]. Nouns are one of the most frequently used word classes in English.